ORGANIC MATTER MATURITY LEVEL OF THE DNIEPER-DONETS BASIN DEPOSITS: UNCONVENTIONAL GAS PROSPECTS - Mikhailov , V.; Yemets, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper provides new findings on vitrinite obtained from well-core samples of the Devonian and Carboniferous sedimentary strata of the oilgas prospective fields, both in the eastern and western sides of the Dnieper-Donets Depression (DDD), with a focus on unconventional hydrocarbon prospecting. The organic matter was identified microscopically and vitrinite reflectance was systematically measured. In the deposits studied, vitrinite represents different types of organic macerals; disseminated vitrodetrinite being still dominant. Measurements of vitrinite reflectance striking off different DDD surfaces reveal high average dispersion means ranging 0.5 to ~7.0%. This characterizes variable level of the organic matter maturity and its different property to generate hydrocarbons. However, in general, the vitrinite reflectance tends to gradually increase with depth, meaning gradual maturation of the organic matter from the younger beds to older ones, and a temperature rise conditioned by a temperature gradient. Organic matter immature to generate significant amount of gaseous hydrocarbons is deposited in the DDD at the depth of 3000 m. However, down the depth of 2100 – 2300 m, the average vitrinite reflectance increases up to the values sufficient to consider organic matter mature, and to generate wet and dry gas. Thus, it is inferred to be prospective to explore for new shale gas deposits below the hypsometric level. On the other hand, the irregular dispersion of organic matter maturation in the DDD necessitates further detailed research, namely, into mapping potentially prospective areas of gas generation.
Keywords: vitrinite; organic matter; hydrocarbons; Dnieper-Donets Depression